Use of the Virtual Environment as a Strategy for Disseminating Information during the COVID-19 Pandemic - Corbo, Letícia Noelle; Marcossi, Michel; Okano, Larissa; de Avila, Marla Andreia Garcia [UNESP]; de Fátima Bimbatti, Karina; Kaeppler, Christoph; Faleiros, Fabiana (SAGE Publications, 2023)
Background: The virtual environment has democratized information and research in the health area, especially during the coronavirus disease 2019 (COVID-19) pandemic. Purpose: This study analyzed the boosting strategies of social networks and identified the most accessed posts from a previously developed and validated information portal aimed at people with disabilities. Methods: This quantitative, cross-sectional, descriptive, exploratory study used Google Analytics® to collect data on origins and access numbers; boost data were obtained from the Facebook® and Instagram® networks themselves, after the end of each boost. Conclusions: Greater interest in publications related to the acquisition of rights for persons with disabilities and about COVID-19 was identified. The virtual environment, especially social networks in Brazil, proved to be a useful tool for disseminating information during the COVID-19 pandemic, highlighting the importance of boosting access to health information. In addition, the investment in social networks was relevant due to the increase in the number of followers on the page. Implications for Practice: Social networks can be a valuable means of disseminating research, improving access to information based on scientific evidence in an inclusive way.
Keywords: access to information; coronavirus; rehabilitation nursing; Social media; social networking